1999
DOI: 10.3109/03093649909071627
|View full text |Cite
|
Sign up to set email alerts
|

The functional use of the reciprocal hip mechanism during gait for paraplegic patients walking in the Louisiana State University reciprocating gait orthosis

Abstract: Reciprocally linked orthoses used for paraplegic walking have some form of linkage between the two hip joints. It has been assumed that flexion of the swinging leg is driven by extension of the stance leg. The aims of this study were to investigate the moments generated around the hip joint by the two cables in a Louisiana State University Reciprocating Gait Orthosis (LSU-RGO). Six (6) subjects were recruited from the Regional Spinal Injuries Centre at Southport, who were experienced RGO users. The cables were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 8 publications
0
13
1
Order By: Relevance
“…Dall et al reported that the reciprocal link has a minimal effect on leg swing. 37 In the present study, at baseline, the compensatory motions were high when walking with the IRGO, but a significant improvement in these parameters was found after 8 weeks of gait training. The children with MMC used their trunk muscles to ambulate with the IRGO.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…Dall et al reported that the reciprocal link has a minimal effect on leg swing. 37 In the present study, at baseline, the compensatory motions were high when walking with the IRGO, but a significant improvement in these parameters was found after 8 weeks of gait training. The children with MMC used their trunk muscles to ambulate with the IRGO.…”
Section: Discussioncontrasting
confidence: 44%
“…36 Dall et al suggested that the reciprocal link is minimally important in leg swing when RGOs were used for walking in paraplegic patients. 37 In addition Johnson et al demonstrated that the use of orthoses and assistive devices alone has limited effects on the improvement walking parameters in children with MMC. In the paraplegic patients, trunk and pelvis motion contributes more to leg swing than elements of the orthosis such as the reciprocal link in the ARGO and IRGO.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the ES-EXO (w), a lack of pelvic shell caused a large rotation range of the trunk and pelvis, which probably required greater muscle force. In the IRGO condition, hip flexion was driven by contralateral hip extension through the reciprocal rocking pelvic band (9). Users usually adopt a flexed trunk posture to ensure stability through increasing the area of support created by the feet and the walker (7).…”
Section: Effects Of Different Un-powered Exoskeletons On Trunk Musclementioning
confidence: 99%
“…The energy consumption of using RGOs reported low rate compared to other mechanical orthoses such as MLOs and HKAFOs, based on the reciprocal section of RGOs announced as the responsible for this result. But the effect of the reciprocal link in providing of the reciprocal motion was demonstrated less [62][63][64]. Using RGOs for SCI patients rather than MLOs is cumbersome due to their bulky structure and using an MLO has high energy consumption compared to RGOs, but MLOs are more user-friendly for people with SCI [15,65].…”
Section: Energy Expenditure Of Spinal Cord Injury Patientsmentioning
confidence: 99%